The Evolution of the Border Army from its Creation until the Establishment of the General Staff (1957 – 1960) - seghiri, mounir (The Algerian Historical Journal, 2026)
One key factor to the success of the Algerian revolution was the armament it had received from the eastern and western borders. The French occupation authorities was well-aware of this and it worked to isolate the borders with electrified lines. In this context, the first nucleus of the Border Army began to form, in response to the increasingly unsuccessful military patrols. As time passed, the borders became a heavy burden, which warranted due attention from the revolution leading bodies, resulting in the development of projects to support the revolution from within. In this paper, we shine light on the creation and the development of one of these projects, the Border Army, examining the bodies established by the Revolutionary Command to run it since 1957, until the establishment of the General Military Command in1960